Evaluation study outcome of augmented reality technology for solving engineering problems in UNITEN: Augmented reality technology for solving engineering problems in UNITEN - Sidhu M.S. (IGI Global, 2023)
Augmented reality; Computer software; Engineering; Flow visualization; User interfaces; Augmented reality technology; Controlled environment; Engineering applications; Engineering problem solving; Interface applications; Tangible user interfaces; Usability; Wilcoxon signed rank test; Problem solving